2007
DOI: 10.1097/01.qmh.0000281058.99929.ea
|View full text |Cite
|
Sign up to set email alerts
|

Financial Impact of Failing to Prevent Surgical Site Infections

Abstract: While matching study patients and control patients requires significant time from financial and clinical staff, this approach and the resulting data analysis strengthened and focused our efforts to prevent future SSIs and aligned initiatives to reduce SSIs with the business case for quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 17 publications
0
61
0
4
Order By: Relevance
“…Although some results are inconclusive, two meta-analyses concluded that vancomycin resistance is associated with greater rates of clinical treatment failure and recurrence, and higher all-cause mortality than infections with susceptibile enterococci. [92,93] The 2005 study by DiazGranados and colleagues concluded that patients with bacteraemia caused by VRE were more likely to die than those with vancomycin-sensitive enterococcal bacteraemia, with a summary odds ratio of 2.52 (95%CI, 1.9 to 3.4). [93] …”
Section: Harm To Patients From Vancomycin-resistant Enterococcimentioning
confidence: 99%
See 2 more Smart Citations
“…Although some results are inconclusive, two meta-analyses concluded that vancomycin resistance is associated with greater rates of clinical treatment failure and recurrence, and higher all-cause mortality than infections with susceptibile enterococci. [92,93] The 2005 study by DiazGranados and colleagues concluded that patients with bacteraemia caused by VRE were more likely to die than those with vancomycin-sensitive enterococcal bacteraemia, with a summary odds ratio of 2.52 (95%CI, 1.9 to 3.4). [93] …”
Section: Harm To Patients From Vancomycin-resistant Enterococcimentioning
confidence: 99%
“…[92,93] The 2005 study by DiazGranados and colleagues concluded that patients with bacteraemia caused by VRE were more likely to die than those with vancomycin-sensitive enterococcal bacteraemia, with a summary odds ratio of 2.52 (95%CI, 1.9 to 3.4). [93] …”
Section: Harm To Patients From Vancomycin-resistant Enterococcimentioning
confidence: 99%
See 1 more Smart Citation
“…In North America, one fourth of hospital-acquired infections are SSI, resulting in billions of dollars in hospitalization costs annually; therefore, major efforts are concentrated on prevention [3][4][5]. A considerable proportion of infants admitted to the neonatal intensive care unit (NICU) require surgical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…2012; 46(6):1483-92 www.ee.usp.br/reeusp/ A systematic review of surgical hand antisepsis utilizing an alcohol preparation compared to traditional products Gonçalves KJ, Graziano KU, Kawagoe JY intRodUction Surgical site infections are the major cause of postoperative morbidity and mortality and represent large costs to hospitals (1) . In spite of the multifactorial cause, molecular biology-based studies have correlated the surgical site infections to the surgical team's hand surgical antisepsis, which may even include outbreaks (2)(3)(4) .…”
Section: Rev Esc Enferm Uspmentioning
confidence: 99%